2020
DOI: 10.1371/journal.pone.0227284
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis clarified genes involved in resistance to Phytophthora capsici in melon

Abstract: Phytophthora blight caused by Phytophthora capsici is a devastating disease for melon plant. However, the underlying resistance mechanisms are still poorly understood. In this study, the transcriptome differences between the resistant ZQK9 and susceptible E31 at 0, 3, and 5 days post-inoculation (dpi) were identified by RNA-seq. A total of 1,195 and 6,595 differentially expressed genes (DEGs) were identified in ZQK9 and E31, respectively. P. capsici infection triggered massive transcript changes in the inocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Several comparative transcriptomic studies have been reported in melon [ 75 – 77 ], but few studies have focused exclusively on expression profiling of R -genes against phytopathogenic agents in melon. For example, RNA-seq assessment of the changes in transcript levels at different time points in Phytophthora capsici -inoculated tissues of resistant and susceptible melon genotypes provided a basis for identifying candidate resistant genes [ 78 ]. Comparative transcriptome analysis identified ten genes that were differentially expressed in resistant and susceptible cultivars of melon in response to powdery mildew [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several comparative transcriptomic studies have been reported in melon [ 75 – 77 ], but few studies have focused exclusively on expression profiling of R -genes against phytopathogenic agents in melon. For example, RNA-seq assessment of the changes in transcript levels at different time points in Phytophthora capsici -inoculated tissues of resistant and susceptible melon genotypes provided a basis for identifying candidate resistant genes [ 78 ]. Comparative transcriptome analysis identified ten genes that were differentially expressed in resistant and susceptible cultivars of melon in response to powdery mildew [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several comparative transcriptomic studies have been reported in melon [75][76][77], but few studies have focused exclusively on expression pro ling of R-genes against phytopathogenic agents in melon. For example, RNA-seq assessment of the changes in transcript levels at different time points in Phytophthora capsici-inoculated tissues of resistant and susceptible melon genotypes provided a basis for identifying candidate resistant genes [78]. Comparative transcriptome analysis identi ed ten genes that were differentially expressed in resistant and susceptible cultivars of melon in response to powdery mildew [79].…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports/ Discussion P. capsici is a destructive pathogen which has caused widespread and devastating damage to the melon industry 4 . In our previous study, one melon inbred line, ZQK9, was identified as highly resistant to P. capsici 14 . Using ZQK9 and another highly susceptible line E31 as the paternal and maternal lines, we constructed the F 1 , F 2 , and BC 1 populations and found the resistance in ZQK9 was controlled by a dominant gene, tentatively named MePhyto.…”
Section: Expression Analysis Of Genes In Target Region the Expressiomentioning
confidence: 99%